THE EFFECT OF PRICE, LOCATION, AND SERVICE QUALITY ON REPEAT PURCHASE DECISIONS IN MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMEs) FESTALS ON SUNDAY ACTIVITIES IN LHOKSEUMAWE CITY - Maryana Br Manik; Mohd. Heikal; Rusydi Abubakar; Ikramuddin (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of price, location, and service quality on repurchase decisions among MSMEs at the Ahad Festival in Lhokseumawe City. The research method applied is quantitative with an associative approach. Data were collected through questionnaires distributed to 125 respondents who had previously made purchases at the Ahad Festival. Instrument testing was carried out using validity and reliability tests, while classical assumption tests included normality, multicollinearity, and heteroscedasticity tests. Data analysis was conducted using multiple linear regression with SPSS version 26. The results indicate that price, location, and service quality have a positive and significant effect on repurchase decisions, both partially and simultaneously. The coefficient of determination (R²) value of 0.376 shows that 37.6% of the variation in repurchase decisions can be explained by the independent variables, while the remaining portion is influenced by other factors outside this research model.